2014
DOI: 10.1002/erv.2309
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Risk Factors for Compulsive Exercise: A Prospective Study of Adolescents

Abstract: Sociocultural risk factors for compulsive exercise:A prospective study of adolescents AbstractThe risk factors for compulsive exercise are unknown. This study aims to explore longitudinal sociocultural risk factors for compulsive exercise, using a 12 month prospective design. A sample of 332 male and female adolescents (aged 13-15 years at baseline) completed self-report measures of sociocultural risk factors and compulsive exercise at baseline and eating disorder psychopathology and compulsive exercise at 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
1
16
2
1
Order By: Relevance
“…Meyer et al’s (2011) model has been supported by several studies in both community (Goodwin et al, 2011, 2012, 2014a,b, 2016) and clinical adolescent groups (Formby et al, 2014; Noetel et al, 2016; Swenne, 2016). Fewer studies have examined a multidimensional function of exercise in adults with EDs.…”
Section: Introductionmentioning
confidence: 81%
“…Meyer et al’s (2011) model has been supported by several studies in both community (Goodwin et al, 2011, 2012, 2014a,b, 2016) and clinical adolescent groups (Formby et al, 2014; Noetel et al, 2016; Swenne, 2016). Fewer studies have examined a multidimensional function of exercise in adults with EDs.…”
Section: Introductionmentioning
confidence: 81%
“…In light of the association between being male and having greater muscle mass, it may be that some trans males will be at risk for other types of body image‐related behaviours, such as body building and excessive exercise and the development of symptoms of muscular dysmorphia or dysmorphic disorders (Nieuwoudt, Zhou, Coutts, & Booker, ). This is well‐documented in the cisgender population with sociocultural messages promoting becoming muscular, predicting compulsive exercise in boys (Goodwin, Haycraft & Meyer, ); and indeed body building, at extreme levels, has been termed ‘bigorexia’ (Mosley, ). Relatedly, for trans females, the influence of desired gender on drive for thinness may reflect what is seen in the general population, with some trans females internalizing the same ideals that some cisgender females do with regard to the ideal female body, possibly because their female identity has been present for many years (reflected in the older age of the trans females attending clinic) (Hoek, ; Witcomb et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a cisgender population, appearance comparisons and internalisations are associated with muscularity-orientated body dissatisfaction and risky body change behaviour (Karazsia & Crowther, 2010). This is evidenced by Goodwin, Haycraft and Meyer (2014) who found that peer and family messages to become more muscular predicted compulsive exercise in teenage boys. In light of the review's findings and previous literature, clinicians working with trans people must be mindful that body dissatisfaction may be driven by gender dysphoria and also by culturally emphasised genderspecific ideals (which are probably unattainable) in order to achieve a more feminine or masculine body shape, depending on their gender identity.…”
Section: Discussionmentioning
confidence: 99%